Parallel time : growing up in black and white - Staples, Brent A., 1951- (Avon Books, 1995)
Parallel Time is an evocative memoir that poses universal questions: Where does the family end and the self begin? What do we owe our families, and what do we owe our dreams for ourselves? What part of the past is a gift and what part a hackle? For Brent Staples there is the added dimension of race: moving from a black world into one largely defined by whites. The oldest son among nine children, Brent grew up in a small industrial town near Philadelphia. First a scholarship to a local college and then one for graduate study at the University of Chicago pulled him out of the close family circle. While he was away, the industries that supported the town failed, and drug dealing rushed in to fill the economic void.